Risk factors of heart disease in nurses - Mahdi K Jahromi; Mohsen Hojat; Saiede R Koshkaki; Faride Nazari; Maryam Ragibnejad (Wolters Kluwer Medknow Publications, 2017)
Background: Identifying and correcting the modifiable risk factors reduces the prevalence of coronary artery disorders (CAD). Nurses, with regards to their employment conditions, can be prone to cardiovascular disease (CVD). This study aimed to determine the prevalence of cardiovascular risk factors among nurses. Materials and Methods: In this cross-sectional study, census sampling was conducted among nurses of Jahrom, Iran, in 2014. Data were collected through interviews, blood pressure measurement, anthropometric parameters, and blood sample collection. To analyze the data, descriptive statistical analysis, and comparative (independent t-test) and correlation (Pearson) tests were used; the significance level was considered to be P < 0.05. Results: In this study, 263 (89.76%) nurses participated, 79.8% of whom were women. The mean age of the participants was 31.04 (6.97). In terms of body mass index, 41.7% was the waist-to-hip ratio, 16.7% was the waist-to-height ratio, and 63.1% were in the range of obesity. In addition, 5.7% had abnormal triglyceride, 4.9% had high cholesterol, and 15.1% had high blood pressure. The mean percentage of the Framingham risk score of the participants was 1.07 (1.84). Conclusions: In this study, the total mean percentage of the Framingham risk score of the nurses was 1.07, which showed a low risk of CAD in the study population over the next decade.